Evaluación de 5 bioinsecticidas aplicados a dos dosis para el control de mosca de la fruta (Anastrepha spp.), en guayaba (Psidium guajava L.), en el barrio Gustavo Andrade, cantón Lago Agrio, provincia de Sucumbíos, 2021 - Balladares Bravo, Kerly Yanela (2021)
The purpose of this research is to evaluate 5 bioinsecticides for the control of fruit flies (Anastrepha spp.), in guava (Psidium guajava L.), in the Gustavo Andrade neighborhood of the Nueva Loja Parish. With an area of 3,128, its height above sea level is 300 meters above sea level, the design for this constitutional study of five excerpts applied in two doses and a witness, using a design entirely at random (DCR). This research aims to identify the best bioinsecticide with its corresponding dose in the ten treatments. Five plants were used for the elaboration of the infusions, which were: husk (Cinchona pubescens Vahl), coca (Erythroxylum coca var. coca), fern (Diplazium caudatum), tropical nettle, Verbena (Verbena litoralis Kunth), and a food attractant in this case molasses was used, the concentrations that were used were 30% and 60%, after performing the method of infusión of each living organism of the five species was administered one cc in each experimental unit. The data were processed in dynamic graphs to determine the best bioinsecticide. The results obtained showed that the best bioinsecticide was the fern (Diplazium caudatum) at a concentration of 30% and an average of 4,03 the interactions between the bioinsecticide proved to have much significance concerning the control. They are decreeing that more information should be collected on the use of these plants for further research.